Carbene and Acid Cooperative Catalytic Reactions of Aldehydes and o-Hydroxybenzhydryl Amines for Highly Enantioselective Access to Dihydrocoumarins - Chen, Xingkuan (2018)
A highly enantioselective method for quick access to dihydrocoumarins is reported. The reaction involves a cooperative catalytic process with carbene and in situ generated Brønsted acid as the catalysts. α-Chloro aldehyde and readily available and stable o-hydroxybenzhydryl amine substrates were used to generate reactive azolium ester enolate and ortho-quinone methide (o-QM) intermediates, respectively, to form dihydrocoumarins with exceptionally high diastereo- and enantioselectivities. The catalytic reaction products can be easily transformed to valuable pharmaceuticals and bioactive molecules.